SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA TEKNISI TERBAIK PADA CV. DIFACOM SOLUSINDO MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Fahrulrozi, Fahmi; Suryadi, Ahmad; Santoso, Budi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
An objective and standardized technician performance evaluation is essential for improving efficiency and service quality in companies. CV. Difacom Solusindo faces challenges due to its current manual and subjective assessment process, which often leads to unfair evaluations and reduced employee motivation. This research aims to design and develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist in evaluating technician performance. The system incorporates five key criteria: discipline, work quality, punctuality, teamwork, and customer feedback. The results demonstrate that the system effectively produces objective, fast, and transparent evaluations, supporting more accurate managerial decision-making.